Dependence on temperature of the effect of dinitrophenol on the release of transmitter quanta at neuromuscular junctions in the mouse diaphragm. - Nishimura, M. (1996)
1. The frequencies (F, s-1) of miniature endplate potentials and the quantal content (m) of endplate potentials were measured intracellularly and simultaneously at mouse diaphragm endplates in a bathing solution that contained 0.6 mM Ca2+ ions and 5 mM Mg2+ ions. 2. Twin pulses at 4 ms intervals gave the quantal contents of the first (m1) and second (m2) responses. The ratio of m2/m1 was taken as an indicator of the temporal facilitation of the release of transmitter. 3. Dinitrophenol (DNP, 10 microM) increased the values of F and m at 36 degrees C. This effect did not depend on extracellular Ca2+ ions. 4. The potentiating effect of DNP disappeared at 24 degrees C but the value of m2/m1 remained constant. 5. These results suggest that the effect of DNP is modifiable by temperature which can affect systems that control the intracellular metabolism of Ca2+ ions.